2023
DOI: 10.3389/fnut.2023.1102225
|View full text |Cite
|
Sign up to set email alerts
|

Exploring plant polyphenols as anti-allergic functional products to manage the growing incidence of food allergy

Abstract: The active substances derived from plants have received increasing attention owing to their wide range of pharmacological applications, including anti-tumor, anti-allergic, anti-viral, and anti-oxidative activities. The allergy epidemic is a growing global public health problem that threatens human health and safety. Polyphenols from plants have significant anti-allergic effects and are an important source of anti-allergic drug research and development. Here, we describe recent advances in the anti-allergic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…In recent years, much attention has been paid to the mechanisms by which polyphenols can exert immunomodulatory actions in allergic diseases. Evidence from in vitro and in vivo studies has highlighted that polyphenols can influence allergic immune response, exhibiting both stimulatory and inhibitory effects at two essential stages, during the sensitization and the effector phase [30][31][32][33][100][101][102][103][104][105][106][107].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent years, much attention has been paid to the mechanisms by which polyphenols can exert immunomodulatory actions in allergic diseases. Evidence from in vitro and in vivo studies has highlighted that polyphenols can influence allergic immune response, exhibiting both stimulatory and inhibitory effects at two essential stages, during the sensitization and the effector phase [30][31][32][33][100][101][102][103][104][105][106][107].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…During the effector phase, re-exposure to the same allergen leads to the cross-linking of IgE bound to FcεRI on the surface of mast cells and basophils causing their activation and degranulation with the release of reactive mediators triggering acute systemic allergic reaction [119]. Recently, numerous in vitro and in vivo studies have investigated the mechanisms through which polyphenols may exert a modulatory effect on mast cells as major effector cells of the allergic reaction [30,31,105]. In addition to aforementioned impact on the expression of the FcεRI receptor and the FcεRI-IgE binding, different polyphenols, such as resveratrol, quercetin, procyanidins from cinnamon or apple extract, can suppress mast cells activation via inhibiting the cross-linking of IgE by allergens on the cell surface [106,144,145].…”
Section: Effector Phasementioning
confidence: 99%
See 2 more Smart Citations
“…Phenolic compounds are also known for their antioxidant properties and confer health advantages by sustaining human physiological well-being, bolstering the body's resilience against oxidative harm, and mitigating the risk of ailments like cardiovascular diseases and cancer [ 5 ]. Studies have revealed that phenolic compounds impart various pharmacological effects, including metal ion chelation [ 6 ], antioxidant properties [ 2 ], vasodilation [ 7 ], anti-allergenic [ 8 ] and anti-inflammatory [ 9 ], antimicrobial [ 6 , 9 , 10 , 11 ], and antitumor properties [ 12 ].…”
Section: Introductionmentioning
confidence: 99%